Analysis of the research about the Fediverse: Mastodon, Lemmy, Pleroma and other fediverse platforms - Lázaro-Rodríguez, Pedro (Infonomy, 2024)
This article presents the results of an analysis of the research about the Fediverse, Mastodon, Lemmy, Pleroma, and other fediverse platforms, considering 60 documents retrieved. Publications increase in 2022 and 2023, coinciding with Elon Musk's arrival on Twitter and the so-called waves of migration to Mastodon. The main type of document is the conference article, followed by scientific journal articles and preprints. Much of the publications are open access or free and English is the main language. On the other hand, the main topic is the nature of the Fediverse and its values of federation, decentralization, openness, and its horizontal structure based on instances. Other important topics are the analysis of contents and consumption, and activism. Finally, the article focuses on the relationship between the scientific community and the Fediverse, commenting on some cases of unethical treatment and collection of data from the people in the Fediverse, and highlighting and thinking about the relationship between the values of the federated universe and those of open science.
Keywords: Fediverse; Mastodon; Lemmy; Pleroma; Social networks; Federation; Decentralization; Instances; Free software; Scientific community; Open science; Scientific evidence